TRAY RESEARCH OF THE STRAIN STATE OF SOIL BASES REINFORCED BY SOIL-CEMENT ELEMENTS UNDER THE STRIP STAMP - Vynnykov, Yuriy; Razdui, Roman; Aniskin, Aleksej (Academic journal Industrial Machine Building Civil Engineering, 2019)
Experimental research of weak bases reinforced by vertical soil-cement elements are discribed in this article. Tray research ofweak clay bases and bases with percent of reinforcement from 2,1% to 7,1% under strip stamp were conduct. As a result ofthe experiment settlements for each of soil base models were obtained. Characteristic curves of the influence of the reinforcement percentage on the bearing capacity, deformability are given, character of settlements of the investigated soil massin time at step-increasing loading are shown. It was found that depending on the percentage of reinforcement the critical pressures increased linearly and the values of settlement at critical pressures were determined increased with the base reinforcement percentage. Empirical dependencies were obtained to determine the critical pressures depending on the percentage ofreinforcement for the investigated soil conditions. In conclusion, the effectiveness of reinforcing the base of the strip foundations by vertical soil-cement elements was proved.
Keywords: loam; rigid strip stamp; settlemen; soil base, tray research; vertical soil-cement element